PENGARUH LOVE OF MONEY DAN IKLIM ETIS ORGANISASI TERHADAP MANAJEMEN LABA: STUDI EKSPERIMENTAL - Wardana, Linda Kusumastuti (Universitas Ahmad Dahlan, 2018)
This study is a 2x2 experiment which aims to test the effects of love of money and the ethical climate of the organization on earnings management. This study used 64 students of Master of Accounting. The student decisions represent manager’s belief on performing earnings management when organizational ethical climate and love of money were presented. ANOVA test results indicate that the degree of love of money affects manager’s belief to perform earnings management, organizational ethical climate affects manager’s belief to perform earnings management, and the influence of love of money interact with ethical climate of organization on the manager’s belief to perform earnings management. Thus, all of hypotheses in this study are supported.